Conversation and transcription activities with synchronous video computer-mediated communication: A classroom investigation. (June 2022) - Loewen, Shawn; Buttiler, Maria; Kessler, Matt; Trego, Daniel
Abstract: As much second language (L2) teaching and learning continues to move online, teachers are increasingly seeking out creative ways to integrate synchronous video computer-mediated communication (SVCMC) technologies such as Zoom and Skype with other types of activities. The current study investigates this issue by exploring pedagogical activities used in a university's existing L2 Spanish program, as it instituted a requirement for its L2 learners to engage in SVCMC conversations. In the study, learners ( N = 35) first engaged in SVCMC conversations with L1 Spanish speakers using TalkAbroad . Then learners completed a transcription activity in which they reflected on their conversations. Using a cognitive-interactionist approach, we investigate the L2 learning potential of these activities by examining: the types of focus on form that occurred in learners' SVCMC sessions; the correspondence between the SVCMC interactions and learners' transcriptions; and the relationship between students' interactions, their focus on form, and their transcriptions, when compared with students' self-reported noticing and learning of linguistic items. Findings suggest that SVCMC can provide opportunities for various types of focus on form that might promote L2 development. Transcription can also lead to self-reported noticing of L2 linguistic features.